2020
DOI: 10.1088/1757-899x/890/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection of reinforcement with phosphate coatings

Abstract: As a method of protection against corrosion, the application of phosphate coatings to the surface of steel reinforcement before the manufacture of a reinforced concrete product can be considered. The influence of modifiers introduced into the cold phosphating solution on the structure and protective properties of phosphate coatings was studied. It is established that from solutions with the addition of saccharin, glucose, Trilon A, Trilon B and washing preparations, fine crystalline, dense phosphate films are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Coatings from phosphate solutions were deposited on samples of steel grade St3 (the chemical composition of steel is shown in Table 1). The surface of the samples was pre-sanded with sanding paper, degreased in 3-5% Na 2 CO 3 solution with the addition of solid soap (1-2%) at a temperature of 50-70 • C for 10 min, and etched in a 5% solution of sulfuric acid for 30 s. To obtain phosphate coatings of white color, it is proposed to additionally introduce zinc and calcium nitrates at the rate of 25-30 g/L into phosphating solutions of the composition, g/L: preparation "Majef"-35-45, Zn(NO 3 ) 2 -50-65, NaNO 2 -3-4, glycerin-1-2, trilon B-6-8, preparation OS-20-5-10 [30].…”
Section: Methodsmentioning
confidence: 99%
“…Coatings from phosphate solutions were deposited on samples of steel grade St3 (the chemical composition of steel is shown in Table 1). The surface of the samples was pre-sanded with sanding paper, degreased in 3-5% Na 2 CO 3 solution with the addition of solid soap (1-2%) at a temperature of 50-70 • C for 10 min, and etched in a 5% solution of sulfuric acid for 30 s. To obtain phosphate coatings of white color, it is proposed to additionally introduce zinc and calcium nitrates at the rate of 25-30 g/L into phosphating solutions of the composition, g/L: preparation "Majef"-35-45, Zn(NO 3 ) 2 -50-65, NaNO 2 -3-4, glycerin-1-2, trilon B-6-8, preparation OS-20-5-10 [30].…”
Section: Methodsmentioning
confidence: 99%
“…The luminophor in the phosphate coating, when the solution is mixed, is distributed more evenly over the surface of the sample and glows brighter when developed under ultraviolet light (Fig. 2 Tests of coatings for corrosion protection by the drip method have shown that the resulting luminous coating has similar protective properties with modified phosphate coatings without luminophor [19,20] (Table 3). By the method of contact corrosion, data were obtained to determine the corrosion rate of steel samples with phosphated coatings (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The lower porosity and grain size of coatings deposited from modified cold phosphating solutions allows them to resist the corrosive effect of the environment on the protected surface for longer [19,20]. The time until the first signs of corrosion appear in films obtained from modified cold phosphating solutions is 2 times less than in coatings obtained by the traditional method.…”
Section: Resultsmentioning
confidence: 99%